Valproate-induced hyperammonemic encephalopathy: the role of clinical pharmacists in medication safety—a case report - Wei Chen; Dong Wang; Wei Fu; Jinpeng Wang; Min Chen; Jun Li; Fei Li (Journal of Medical Case Reports)
Abstract Background Sodium valproate, a commonly prescribed antiepileptic drug in clinical practice, has been occasionally linked to hyperammonemia, although the precise mechanisms underlying this adverse effect remain poorly understood. This article reports a case of hyperammonemic encephalopathy induced by sodium valproate in a patient with epilepsy. Through a comprehensive analysis and discussion of appropriate interventions, we aim to offer valuable insights for optimizing antiepileptic drug therapy in clinical settings, thereby preventing adverse drug reactions and ensuring optimal treatment outcomes for patients. Case presentation A 37-year-old Chinese male presented with a complex neurological history. He underwent emergency neurosurgical intervention under general anesthesia 4 years prior to admission for resection of intracranial vascular malformation, evacuation of intracranial hematoma, and decompressive craniectomy following a ruptured right cerebral vascular malformation with hemorrhage, complicated by left frontal–temporal–parietal epidural hematoma and cerebral herniation. Postoperatively, the patient remained in a confusional state. Approximately 2 weeks before the current admission, he developed febrile episodes accompanied by intermittent seizures, leading to hospitalization. The patient was diagnosed with cerebral hemorrhage sequelae and secondary epilepsy, for which sodium valproate therapy was initiated. Despite antiepileptic treatment, seizure control was inadequate, and the patient’s consciousness level progressively deteriorated. Therapeutic drug monitoring revealed a trough valproate concentration of 62 μg/mL, while serial blood ammonia measurements demonstrated a progressive elevation, peaking at 248.1 μmol/L. On the basis of these findings, a diagnosis of sodium valproate-induced hyperammonemic encephalopathy was established. Consequently, sodium valproate was discontinued and replaced with levetiracetam, accompanied by ammonia-lowering therapy. Following this therapeutic adjustment, the patient’s clinical course showed marked improvement: blood ammonia levels decreased to 75.2 μmol/L within 5 days, seizure activity diminished, consciousness level improved, and the patient’s condition stabilized. Conclusion The clinical pharmacy team demonstrated exceptional vigilance in promptly identifying the adverse drug reactions and establishing effective interdisciplinary communication with the attending physicians. This timely intervention and collaborative approach significantly contributed to the optimization of pharmacotherapy, thereby ensuring medication safety and providing a solid foundation for the patient’s favorable therapeutic outcome.